Planning for a sustainable food system. The potential role of urban agriculture in Lisbon Metropolitan Area - Marat-Mendes, T.; Borges, J.C.; Mélice, A.; Lopes, R. (Journal of Urbanism, 2021)
A sustainable transition of planning practices is paramount for municipalities to improve urban environments. Shelter, mobility, and food constitute three basic human needs, which any inhabitant depends on, but attention placed by planning authorities to each differs. The spatial implications of these needs are fundamental for urban design and planning practices. This article ascertains how Portuguese municipal planning has integrated food system concerns and urban agriculture, including design typologies. Starting from a critical perspective on the current land-uses of the Lisbon Metropolitan Area (LMA) and from case-studies of existing urban agriculture examples, this article shows that to promote urban resilience, one needs to account for the food system and use urban design as a tool for optimizing the role of mixed land-uses in urban environments, opportune for a sustainable transition of the LMA.